2009
DOI: 10.1182/blood-2008-06-165522
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD3 preconditioning separates GVL from GVHD via modulating host dendritic cell and donor T-cell migration in recipients conditioned with TBI

Abstract: Host dendritic cells (DCs) play a critical role in initiating graft-versus-host disease (GVHD) and graft-versus-leukemia (GVL), and separation of GVL from GVHD remains a major challenge in the treatment of hematologic malignancies by allogeneic hematopoietic cell transplantation (HCT). Here, we show that preconditioning with anti-CD3 monoclonal antibody before conditioning with total body irradiation (TBI) prevents GVHD but retains GVL in a HCT model of major histocompatibility complex (MHC)-mismatched C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…Still, some other mechanisms might also play a role. Anti-CD3 can regulate the expression of chemokine receptors, as well as target organ protective molecules, such as B7H1 and indoleamine 2,3-dioxygenase (9,13) . Further research is necessary to determine the mechanisms underlying the improvement of TA-GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, some other mechanisms might also play a role. Anti-CD3 can regulate the expression of chemokine receptors, as well as target organ protective molecules, such as B7H1 and indoleamine 2,3-dioxygenase (9,13) . Further research is necessary to determine the mechanisms underlying the improvement of TA-GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, large doses of glucocorticoids and immune inhibitors (such as CsA and CTX) were used to treat TA-GVHD. Recently, anti-CD3-based conditioning regimen was reported to separate GVL from GVHD in animal models (13) . Subsequently, we tested these treatments.…”
Section: Establishment Of Mhc-mismatched Ta-gvhd Model By Splenocyte mentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies for CD24(30-F1), CD4(GK1.5), IgM(II/41) IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), BP1(6C3), CD19(eBio1D3), CD43(eBioR2/60), and CD23(B3B4) as well as efluor 450-labeled streptavidin were purchased from eBioscience (San Diego, CA). Dead cells were excluded using DAPI or aqua fluorescent reactive dye (Invitrogen, Carlsbad, CA).…”
Section: Flow Cytometry and Antibodiesmentioning
confidence: 99%
“…We have demonstrated that induction of mixed chimerism via hematopoietic cell transplantation (HCT) is an effective therapy to reverse autoimmune T1D in NOD mice, using a radiation-free nontoxic anti-CD3/CD8 conditioning regimen (19)(20)(21)(22)(23)(24)(25)(26). Induction of chimerism…”
mentioning
confidence: 99%